Pre-Matrical Nutrition Counseling, Anthropometric and Hemoglobin Examination In Women Of Fertile Age - Huntari Harahap; Armaidi Darmawan; Tia Wida Ekaputri; Erny Kusdiyah; Mirna Marhami Iskandar; Firmansyah (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
ABSTRACT Background: The government's stunting prevention measures begin with improving nutrition, namely during adolescence, in the case of prospective brides, pregnant women, postpartum mothers, and toddlers. Empowerment for women in the community or at home is expected to reduce stunting problems and various child health problems. This study aims to screen for risk factors and prevent stunting in women of childbearing age. Methods: Thirty-six women of childbearing age attended this research activity in the Olak Kemang Health Center working area. The activities included pre-marital nutrition education for women of childbearing age, examination of weight, height, arm circumference, and measurement of blood haemoglobin. Results: The body mass index of Women of Childbearing Age was the most in the thin category, namely 39% (BMI <18.5), haemoglobin levels >12 as much as 58,33%, upper arm circumference above 22 as much as 78% and there was an increase in knowledge assessed from the results of the pretest and posttest, it is known that the average pretest value is 60, and the posttest value is 80. Conclusion: Management of iron tablet administration is needed for women of childbearing age who experience anaemia and increased nutritional intake in women of childbearing age. Keywords: nutrition counseling; anthropometry; hemoglobin; Women of Childbearing Age (WCA); stunting